2005
DOI: 10.1080/00016480510037023
|View full text |Cite
|
Sign up to set email alerts
|

Canalolithiasis of the superior semicircular canal: an anomaly in benign paroxysmal vertigo

Abstract: According to the canalolithiasis theory, benign paroxysmal vertigo (BPPV) is caused by gravity-dependent movements of otoconial debris that collects in the endolymph of the posterior semicircular canal. Other parts of the vestibular organ are rarely affected, and it is mainly the horizontal canal that is affected by this atypical form of BPPV. Canalolithiasis of the superior semicircular canal must be considered an anomaly because the superior semicircular canal is the highest point of the vestibular organ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…nodulus lesion) [21]. Using high-resolution 3D MRI, Schratzenstaller et al [22] found morphological abnormality at the top of the superior semicircular canal (generating a stop to free floating otoconia) in patients with AC-BPPV resistant to therapy, particularly in patients with previous ear surgery or ear disease.…”
Section: Discussionmentioning
confidence: 98%
“…nodulus lesion) [21]. Using high-resolution 3D MRI, Schratzenstaller et al [22] found morphological abnormality at the top of the superior semicircular canal (generating a stop to free floating otoconia) in patients with AC-BPPV resistant to therapy, particularly in patients with previous ear surgery or ear disease.…”
Section: Discussionmentioning
confidence: 98%
“…As there is only one report on this form of posttraumatic BPPV in the literature to the best of our knowledge (19), these 2 cases are presented in greater detail here:…”
Section: Resultsmentioning
confidence: 98%
“…To the best of our knowledge, there has only been 1 report about posttraumatic combined AC/PC BPPV of the same labyrinth so far (19). The authors demonstrated ipsilateral posterior and AC ''filling defects'' using highresolution MRI in a patient with BPPV symptoms after head trauma.…”
Section: Involvement Of the Different Semicircularmentioning
confidence: 93%
See 2 more Smart Citations